Изучение окислительных процессов при глаукоме - Л. М. Овсепян; А. В. Зангинян; Г. С. Казарян (Հայաստանի ԳԱԱ)
Արդի ժամանակներում բաց անկյունային գլաուկոմայի ախտածնությունը մինչև վերջ դեռևս ուսումնասիրված չէ: Աշխատանքի նպատակն էր ուսումնասիրել գլաուկոմայի ժամանակ ընթացող օքսիդային գործընթացները: Որոշվել է սպիտակուցների օքսիդային մոդիֆիկացիաները, լիպիդների գերօքսիդների և ազոտի օքսիդի պարունակությունը գլաուկոմայով հիվանդների արյան պլազմայում: Ուսումնասիրությունների արդյունքում բացահայտվեց, որ հիվանդությունն ընթանում է սպիտակուցների օքսիդային մոդիֆիկացիաների, ինչպես նաև լիպիդների գերօքդիդների և ազոտի օքսիդի պարունակության ավելացմամբ: Ստացված արդյունքները վկայում են, որ հիվանդությունն ուղեկցվում է ազատ ռադիկալային գործընթացների ակտիվացմամբ, որը բերում է օքսիդային սթրեսի զարգացմանը:Pathogenic mechanism of primary open-angle glaucoma has not been fully researched yet. It has been demonstrated the role of oxidation in biological membranes in normal metabolism in the etiology and pathogenesis of many diseases. The aim of this work was to study the oxidative processes in glaucoma. Oxidative modification of proteins, the content of lipid peroxides were determined in the blood plasma of glaucoma patients. The analysis of the levels of oxidative modification of proteins has shown that glaucoma is characterized by increased levels of products of oxidative modification of proteins. The investigation of the content of lipid peroxides and nitric oxide showed an increase of their level in the blood plasma of patients with glaucoma. The findings suggest an activation of free-radiсial processes in glaucoma, leading to the development of oxidative stress.
Keywords: Medicine; Ophthalmology